RIGHT TO GOOD ADMINISTRATION IN BOSNIA AND HERZEGOVINA, WITH FOCUS ON HUMAN RIGHTS - Vranješ, Nevenko D.; Bojan Vlaški, Bojan (Politeia, 2023)
Good administration, good government, and good governance are the latest institutes of the rule of law and the state of law. In order to set up an administration model which would, first of all, be dedicated to citizens and to meeting their needs, their status, and their state, the principles of good administration need to be not only accepted but also operationally transposed into the domestic political and legal system. It needs to be stressed that good administration is becoming the leading model in administrative activity of both international organisations and national administrative and legal systems. The scope of work is the right to good administration in Bosnia and Herzegovina, with focus on human rights. An overview of the operationalisation of principles of good administration in Bosnia and Herzegovina is provided in the second part of the paper, through the human rights perspective. The main hypothesis in the paper is that good administration contributes to the rights of citizens but is insufficiently operationalised in the domestic administrative and legal framework, and that there are major violations of the right of citizens to good administration in Bosnia and Herzegovina. Legal exegesis method, comparative and statistical methods are predominantly used in the paper.